Temporary works : principles of design and construction - Grant, Murray; Pallett, Peter F. (ICE Publishing, 2012)
"Temporary Works: Principles of Design and Construction is the first reference book to deliver authoritative and comprehensive guidance on temporary works for practising engineers."--P. [4] of cover.